Food industry R & D a new approach - Traitler, Helmut; Coleman, Birgit; Burbidge, Adam (John Wiley & Sons, 2017)
"This book discusses the history and background of today's food industry R&D as seen by consumers, academia and the industry itself, with several chapters dedicated to new and disruptive approaches. A must-read for all professionals in the packaged goods industry as well as students who aspire to contribute to this new industry, forcefully driven by R&D."--Provided by publisher.